Sustainable Tourism Development and its Economic Impact on Emerging Economies - Muhammad Bin Ali; Aisha Binti Abdullah; Lee Wei Ming (Universitas Kristen Indonesia Toraja, 2024)
Sustainable tourism is a key driver of economic growth in emerging economies. This research examines the economic, social, and environmental impacts of sustainable tourism initiatives in Southeast Asia. Policy recommendations are provided to promote community-based tourism while preserving natural and cultural heritage.